Analyzing integrated knowledge, attitudes and practices for the adoption of blast-resistant wheat varieties in Bangladesh: A structural equation modeling approach - Nasima Akter; Hasneen Jahan; Md Abdullah Al Noman; Md Monirul Islam; M. Wakilur Rahman; Sadika Haque; Pawan Kumar Singh; Muhammad Rezaul Kabir; Nanda Dulal Kundu (Crop Protection, 2026)

Advances and challenges in goat milk authentication: Integrating rapid and conventional methods for industrial and smallholder systems - A. Ita Juwita; Nanda Triandita; Muhammad Fakih Kurniawan; Slamet Hadi Kusumah; Sri Winarsih; Agung Saputra (International Dairy Journal, 2026)

Developing in vitro propagation systems for Curcuma sumatrana Miq.: a strategy for conserving and utilising an endemic sumatran wild-turmeric species - Apriliana Dyah Prawestri; Nada Maiza Arpita; Mimma Latifah Daraquthni; Annisa Putri Amalia Ma’ruf; Setia Nanda Ariana; Surya Diantina; Popi Aprilianti; Deritha Ellfy Rantau; Sitti Fatimah Syahid; Ratna Uli Damayanti Sianturi; Yosephin Martha Maria Anita Nugraheni; Marlina Ardiyani; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Population genetics of climbing perch, Anabas testudineus (Bloch, 1792) in the waters of Aceh Province, Indonesia - Nanda Muhammad Razi; Sri Riska Rahayu; Luvi Syafrida Handayani; Mutia Ramadhaniaty; Adrian Damora; Cut Tria Aswina; Putri Khairani Amalia Siregar; Nanda Ulfa Khaira; Muhammad Syukran; Puncak Joyontono; Muhammad Nasir; Nur Fadli; et al. (Ecological Genetics and Genomics, 2026)

Evaluating atmospheric and sun‑glint corrections for Sentinel‑2 total suspended matter mapping in the Northern Waters of Aceh - Yudi Haditiar; Muhammad Ikhwan; Haekal Azief Haridhi; Muhammad Nanda; Syahrul Purnawan; Maria Ulfah (Advances in Space Research, 2026)

Mapping of buried archaeological ruins using magnetic and gravity methods around the 17th-century fort of Gunong Biram, Aceh Besar, Indonesia - Amir Asyqari; Nazli Ismail; Muhammad Nanda; Tomi Afrizal; Muhammad Yanis; Deni Sutrisna; Repelita Wahyu Oetomo; Cut Dewi (Geosciences Journal, 2026)

Identification of Heat-Tolerant Impatiens platypetala Genotypes: Morphological Responses and Stress Tolerance Indices Under Elevated Temperatures - Suskandari Kartikaningrum; Minangsari Dewanti; Safani Ariyantika; Dani Nurdina; Herni Shintiavira; Dewi Pramanik; Fitri Rachmawati; Mawaddah; Dedeh Siti Badriah; Erniawati Diningsih; Hanudin; Wakiah Nuryani; et al. (Agricultural Research, 2026)

Understanding the Cross-Equatorial Pathway: How Tropical Variability Modulates the Propagation of East Asian Cold Surges into the Southern Hemisphere - Narizka Nanda Purwadani; Muhammad Rais Abdillah; Nining Sari Ningsih; Erma Yulihastin (Advances in Atmospheric Sciences, 2026)

An Integrated GRI-SCOR Framework for Assessing Green Purchasing Disclosure and Implementation in Manufacturing: A NVivo-Based Content Analysis - Elisa Kusrini; Putri Dwi Annisa; Duta Nanda Rusmana; Muhammad Irfan Mumtaza; Rangga Primadasa (Circular Economy and Sustainability, 2026)

Morphometric and genetic variation of six soldierfish species (genus Myripristis, family: Holocentridae) harvested in Aceh Besar waters, Indonesia - Nadya Tirta; Essy Harnelly; Rania Feranita Fachri; Putri Khairani Amalia Siregar; Nanda Muhammad Razi; Nanda Ulfa Khaira; Mutia Ramadhaniaty; Sri Riska Rahayu; Nurlita Putri Anggraini; Raissha Amanda Siregar; Adrian Damora; Nur Fadli (Zoologischer Anzeiger, 2026)

Genetic Population of Rusty Jobfish Aphareus Rutilans (Cuvier, 1830), Including a New Sequence Record from South Aceh Waters Indonesia - Sri Riska Rahayu; Abdul Rahman Siregar; Mutia Ramadhaniaty; Nanda Muhammad Razi; Syamsul Rizal; Nur Fadli; Luvi Syafrida Handayani; Martin Wilkes; Mohd Nor Siti-Azizah; Su-fang Niu; Zainal Abidin Muchlisin (Thalassas: An International Journal of Marine Sciences, 2025)

DNA barcoding of fish from Singkil peat swamp waters of Aceh Province, Indonesia - Nanda Muhammad Razi; Sri Riska Rahayu; Luvi Syafrida Handayani; Nanda Ulfa Khaira; Muhammad Syukran; Ahmad Sazali A. Sitorus; Cut Tria Aswina; Putri Khairani Amalia Siregar; Muhammad Nasir; Nur Fadli; Martin Wilkes; Mohd Nor Siti-Azizah; et al. (Zoologischer Anzeiger, 2025)

How shallow solum shapes plant selection, tree diversity, carbon stocks and earthworms in coffee agroforestry - Rika Ratna Sari; Muhammad Naufal Ramadhan; Nadiyah Rifdatun Nailah; Nanda Ardiansyah; Ahmad Ali Yuddin Fitra; Arif Firmansyah; Rizki Maulana Ishaq; Danny Dwi Saputra (Agroforestry Systems, 2025)

A comparative study of fully automatic and semi-automatic methods for oil spill detection using Sentinel-1 data - Muhammad Iqbal Habibie; Hariyanto; Robby Arifandri; Zulfa Qonita; Pronika Kricella; Muh Hisyam Khoirudin; Noor Muhammad Ridha Fuadi; Nurul Shabrina; Nanda Itohasi Gutami; Siti Sadiah; Dewi Kartikasari; Muh.Mulyadi Agus Widodo; et al. (Environmental Monitoring and Assessment, 2025)

Physiological characteristics of ornamental caladiums (Caladium x hortulanum Birdsey, Araceae Juss.) through leaf colour diversity - Rahmat Budiarto; Syariful Mubarok; Jajang Sauman Hamdani; Muhammad Achirul Nanda; Moh Haris Imron S Jaya; Siti Auliya Rahma; Muhamad Abdul Rofiq; Supatida Abdullakasim (South African Journal of Botany, 2024)

Detection and monitoring techniques of termites in buildings: A review - Babar Hassan; Muhammad Achirul Nanda (International Biodeterioration & Biodegradation, 2024)

The first outbreak of Lumpy Skin Disease in Indonesia - Widi Nugroho; Hani Muhamad Mardani; Michael Philipp Reichel; Yul Fitria; Yuli Miswati; Niko Febrianto; Muhammad Edy Nuryanto; Intan Apriana; Nur Azzahrawani; Eno Martalina; Shelly Kusumarini; Hermanto; et al. (Tropical Animal Health and Production, 2024)

Growth Patterns, Condition Factor, and Population Dynamics of Snapper Lutjanus bengalensis and Lutjanus lutjanus (Pisces: Lutjanidae) Harvested from Aceh Waters Indonesia - Sri Riska Rahayu; Syamsul Rizal; Nur Fadli; Ilham Raza; Muhammad Isran Lazuardi; Luvi Syafrida Handayani; Nanda Muhammad Razi; Martin Wilkes; Mohd Nor Siti-Azizah; Zainal A. Muchlisin (Thalassas: An International Journal of Marine Sciences, 2024)

Assessing the sustainability of threadfin bream fishery along South-eastern coast of the Arabian Sea: A comprehensive analysis of climate change impact and fishing frontiers - Radhika Balachandran; P.U. Zacharia; G.B. Purushottama; K.S. Sudarsan; Muhammad Shafeeque; R. Ratheesh Kumar; Eldho Varghese; Alphonsa Joseph; R. Rahul; Nanda Kishore; Rose P. Bright; P.K. Seetha; et al. (Regional Studies in Marine Science, 2024)

Oceanographic characteristics in the North of Aceh waters - Yudi Haditiar; Muhammad Ikhwan; Saiful Mahdi; Ananda Novita Siregar; Haekal Azief Haridhi; Ichsan Setiawan; Muhammad Nanda; Vicky Prajaputra; Muhammad Irham (Regional Studies in Marine Science, 2024)

Morphometric and genetic variations of three grouper species (genus Epinephelus) from the northern region of Aceh province, Indonesia - Nur Fadli; Adrian Damora; Zainal Abidin Muchlisin; Mutia Ramadhaniaty; Nanda Muhammad Razi; Sri Riska Rahayu; Edison D. Macusi; Ahasan Habib; Mohd N. Siti-Azizah (Zoologischer Anzeiger, 2023)

Morphometric and genetic variations of four dominant species of snappers (Lutjanidae) harvested from the Northern Coast of Aceh waters, Indonesia - Sri Riska Rahayu; Zainal A. Muchlisin; Nur Fadli; Nanda Muhammad Razi; Mutia Ramadhaniaty; Luvi Syafrida Handayani; Siti Maulida; Firman M. Nur; Nurlaili Nurlaili; Moh N. Siti-Azizah (Zoologischer Anzeiger, 2023)

In-situ electro-stimulation enhanced branching but not massive scleractinian coral growth - Munandar Samidon; Nanda Muhammad Razi; Muhammad Agustiar; Puad Batari Harahap; Nurul Najmi; Samsul Bahri; Shang Yin Vanson Liu (Frontiers in Marine Science, 2022)
Calcium carbonate (CaCO 3 ) is the main component of the skeleton of scleractinian corals and is a preferable substrate for attachment and growth. An electro-stimulation method based on the electrolysis of seawater, which generates calcium and magnesium minerals as a crystalline coating over artificial metal structures, was used to boost coral growth during the 1970s. Few studies have attempted to compare survival and growth between electro-stimulated corals and non-electro-stimulated corals in situ . In this study, we used 2D image analysis to quantify the growth of branching and massive corals on electro-stimulated structures. Among four metallic structures that were deployed in Sabang, Aceh, Indonesia, three were electro-stimulated (12 V) and one was used as a control. Two branching corals ( Acropora gemmifera and Pocillopora verrucosa ) and two massive coral species ( Porites murrayensis and Porites lobata ) were selected. A total of 256 fragments, comprising 128 fragments derived from two branching species and 128 fragments derived from two massive species, were randomly dispatched to each structure. Underwater photographs were taken at three intervals from August 2019 to December 2020. The results showed that the survival rates (excluding lost fragments) of branching corals under electro-stimulation were approximately 19% higher than massive. However, no significant difference was found between the survival rates of the treatment and control groups for both branching and massive corals. Furthermore, we found that under electro-stimulation, branching corals grew faster than controls but not massive. Our study provides pieces of evidence for the potential use of electrochemical processes in stimulating the growth of branching corals.